Assessing the Role of Nursing Professionals in the Delivery of Integrated Primary Health Care - Ardesa, Yopi Harwinanda; Setyorini, Yuyun; Anggit Jiwantoro, Yudha; Sulistya Affarah, Wahyu; Firdausi Paramaiswari, Nurul; Darawati, Made (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: The integration of Primary Health Care (PHC) services is crucial for improving health outcomes and efficiency in health systems globally. Nursing professionals play a critical role in delivering these integrated services. Understanding their contribution and the impact of their involvement is essential for optimising PHC delivery. The objective of this systematic review is to evaluate the roles and contributions of nursing professionals in the delivery of integrated primary healthcare services. Methods: A comprehensive search strategy will be implemented across electronic databases, including PubMed, CINAHL, and Cochrane Library, to identify relevant studies. Studies published from [start date] to [end date] will be considered. Two independent reviewers will screen titles and abstracts for eligibility, followed by a full-text review of potentially relevant articles. Data extraction and quality appraisal will be conducted using standardised forms. A narrative synthesis will be performed to analyse and summarise the findings. Conclusion: This systematic review will provide evidence on the contributions of nursing professionals to integrated primary health care delivery. The findings will recommend policy and practice in primary health care services.